Interlinear and Marginal Glosses in the Athonite Translation of John Chrysostom’s De Statuis - Aneta Dimitrova (Studia Ceranea)
According to a colophon in manuscript RM 3/6 from the Rila Monastery, a complete Slavonic translation of John Chrysostom’s Homilies on the Statues was made on Mount Athos by the Serbian monk Antonije and copied by Vladislav the Grammarian in 1473. In fact, this is the earliest extant copy of a thorough revision of the first translation that was made in Preslav in the 10th century, and the text was partially translated anew after a different Greek source. All three preserved copies of this translation contain a number of explanatory glosses. Some of them refer to rare and archaic words, whereas others provide synonyms and better readings. In the article, close attention is paid to the 21 interlinear and marginal glosses as they occur in the Rila manuscript. The glosses are divided into four overlapping groups: I. Translations and explanations of Greek words; II. Biblical references; III. Synonyms; and IV. Varia. Eight of the annotations are discussed in detail in comparison to the Preslav translation and the Greek sources, with additional data from other medieval Slavonic texts. Since the practice of annotating was typical of the scribe Vladislav, some arguments were considered whether he was the author of the glosses. In most cases, the annotator was also a competent and observant editor, who usually corrected or updated the language according to his contemporary terminology.